Kidney Transplant Recipients Carrying the CYP3A4*22 Allelic Variant Have Reduced Tacrolimus Clearance and Often Reach Supratherapeutic Tacrolimus Concentrations. Issue 3 (14th January 2015) - Pallet, N.; Jannot, A.‐S.; El Bahri, M.; Etienne, I.; Buchler, M.; de Ligny, B. H.; Choukroun, G.; Colosio, C.; Thierry, A.; Vigneau, C.; Moulin, B.; Le Meur, Y.; et al.
<x xml:space="preserve">Abstract</x> CYP3A4*22 is an allelic variant of the cytochrome P450 3A4 associated with a decreased activity. Carriers of this polymorphism may require reduced tacrolimus (Tac) doses to reach the target residual concentrations (Co). We tested this hypothesis in a population of kidney transplant recipients extracted from a multicenter, prospective and randomized study. Among the 186 kidney transplant recipients included, 9.3% (18 patients) were heterozygous for the CYP3A4*22 genotype and none were homozygous (allele frequency of 4.8%). Ten days after transplantation (3 days after starting treatment with Tac), 11% of the CYP3A4*22 carriers were within the target range of Tac Co (10–15 ng/mL), whereas among the CYP3A4*1/*1 carriers, 40% were within the target range (p = 0.02, OR = 0.19 [0.03; 0.69]). The mean Tac Co at day 10 in the CYP3A4*1/*22 group was 23.5 ng/mL (16.6–30.9) compared with 15.1 ng/mL (14–16.3) in the CYP3A4*1/*1 group, p < 0.001. The Tac Co/dose significantly depended on the CYP3A4 genotype during the follow‐up (random effects model, p < 0.001) with the corresponding equivalent dose for patients heterozygous for CYP3A4*22 being 0.67 [0.54; 0.84] times the dose for CYP3A4*1/*1 carriers. In conclusion, the CYP3A4*22 allelic variant is associated with a significantly altered Tac metabolism and carriers of this polymorphism often reach supratherapeutic concentrations.